Combined method for the evaluation of the initial and late phases of the apoptosis process in prepubertal rat testes - Vázquez-Nin, Gerardo Hebert; ML, Escobar; OM, Echeverría; R, Ortiz; HG, Márquez; S, Juárez (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Apoptosis is a physiological process that maintains tissue homeostasis. This study used testes from pre-pubertal Wistar rats to evaluate the initial and late phases of germ cell alterations. We used toluidine blue staining and immunodetection of active caspase-3 in semi-thin sections, as well as electron microscopy techniques to determine the ultrastructural modifications that correspond to initial or advanced cellular damage. Our qualitative results from optical observations showed that the general stains permit identification of the advanced stages of apoptosis; however, the more sensitive techniques of immunolocalization as well as the electron microscopy also revealed the initial phases of apoptosis. The ultrastructural evidence not only confirms the observations made with the optical techniques, but also allowed the identification of the earliest morphological sign of cell elimination as nuclear envelope and mitochondrial dilatation. Our observations indicate that the combined use of the techniques of light and electron microscopy permits better identification of the initial alterations of the process of cell death in the testes.